Adaptation of a mobile phone health survey for risk factors for noncommunicable diseases in Colombia: a qualitative study. Issue 1 (31st December 2020) - Torres-Quintero, Angelica; Vega, Angela; Gibson, Dustin G.; Rodriguez-Patarroyo, Mariana; Puerto, Stephanie; Pariyo, George W.; Ali, Joseph; Hyder, Adnan A.; Labrique, Alain; Selig, Hannah; Peñaloza, Rolando Enrique; Vecino-Ortiz, Andres I.
ABSTRACT: Background: Data collection on noncommunicable disease (NCD) behavioral risk factors has traditionally been carried out through face-to-face surveys. However, its high costs and logistical difficulties can lead to lack of timely statistics for planning, particularly in low and middle-income countries. Mobile phone surveys (MPS) have the potential to fill these gaps. Objective: This study explores perceptions, feasibility and strategies to increase the acceptability and response rate of health surveys administered through MPS using interactive voice response in Colombia. Method: A sequential multimodal exploratory design was used. We conducted key informant interviews (KII) with stakeholders from government and academia; focus group discussions (FGDs) and user-group tests (UGTs) with young adults and elderly people living in rural and urban settings (men and women). The KII and FGDs explored perceptions of using mobile phones for NCD surveys. In the UGTs, participants were administered an IVR survey, and they provided feedback on its usability and potential improvement. Results: Between February and November 2017, we conducted 7 KII, 6 FGDs (n = 54) and 4 UGTs (n = 34). Most participants consider MPS is a novel way to explore risk factors in NCDs. They also recognize challenges for their implementation including security issues, technological literacy and telecommunications coverage, especially in rural areas. It was recommended to promote the survey using mass media before its deployment and stressing its objectives, responsible institution and data privacy safeguards. The preferences in the survey administration relate to factors such as skills in the use of mobile phones, age, availability of time and educational level. The participants recommend questionnaires shorter than 10 minutes. Conclusions: The possibility of obtaining data through MPS at a population level represents an opportunity to improve the availability of risk-factor data. Steps towards increasing the acceptability and overcoming technological and methodological challenges need to be taken.